1986
DOI: 10.1093/jn/116.7.1326
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Intake during Pregnancy and Lactation in Rats: Maternal and Pup Hematological Parameters and Liver Iron, Zinc and Copper Concentration

Abstract: To study the effects of maternal coffee intake on trace element status of the fetus and newborn, Sprague-Dawley female rats were fed a control purified diet and were provided ad libitum a freeze-dried coffee solution (1.5% wt/vol) (C) or distilled water (W) as their sole source of liquids from d 0 of gestation. On d 21 of gestation, a subsample of dams from each group was killed and litters were removed for examination. At birth, a subsample of litters from each group was cross-fostered to differentiate betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Cohen and Booth (1975) observed ingestion of coffee increased gastric acid secretion; this could result in more iron being in the ferrous state and hence could promote absorption. Similarly Muñoz et al (1986) observed 3-day-old pups of rats given coffee throughout gestation and lactation had elevated concentrations of iron in their livers. However, these changes probably reflect the smaller size of rats fed coffee in study 1 because the dietary treatments did not affect the total amount of iron in the livers or kidneys of rats.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Cohen and Booth (1975) observed ingestion of coffee increased gastric acid secretion; this could result in more iron being in the ferrous state and hence could promote absorption. Similarly Muñoz et al (1986) observed 3-day-old pups of rats given coffee throughout gestation and lactation had elevated concentrations of iron in their livers. However, these changes probably reflect the smaller size of rats fed coffee in study 1 because the dietary treatments did not affect the total amount of iron in the livers or kidneys of rats.…”
Section: Resultsmentioning
confidence: 64%
“…Rather we hypothesize that ingestion of coffee disturbed iron metabolism during hematopoesis or during iron transport and mobilization perhaps by interfering with copper utilization. Similarly Muñoz et al (1986) recently suggested that maternal coffee intake impaired mobilization of minerals from the liver reserves of pups and thus interfered with hematopoesis.…”
Section: Resultsmentioning
confidence: 97%
“…Coffee intake during pregnancy and lacta tion had no effect on the zinc content of the pup's liver at day 14 [26]. Because coffee contains other metabolically active sub stances in considerable amounts [27,28], it is possible that the pure caffeine added to the maternal diet in this study could have differ ent effects from the coffee.…”
Section: Discussionmentioning
confidence: 88%